2021
DOI: 10.3748/wjg.v27.i21.2710
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations in pancreatic tumors

Abstract: Genetic alterations in pancreatic tumors can usually be classified in: (1) Mutational activation of oncogenes; (2) Inactivation of tumor suppressor genes; and (3) Inactivation of genome maintenance genes controlling the repair of DNA damage. Endoscopic ultrasound-guided fine-needle aspiration has improved pre-operative diagnosis, but the management of patients with a pancreatic lesion is still challenging. Molecular testing could help mainly in solving these “inconclusive” specimens. The introduction of multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 131 publications
(167 reference statements)
0
15
0
1
Order By: Relevance
“…Structural variation, gene mutation and gene copy number alteration are important factors affecting gene expression and function, and are closely related to the activation of oncogenes or the inactivation of tumor suppressor genes ( Malhotra et al, 2013 ; Schaefer et al, 2019 ; Visani et al, 2021 ). The results of pan-cancer analysis showed that the USP45 gene had a low frequency of structural variants, mainly present in PRAD and LIHC ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Structural variation, gene mutation and gene copy number alteration are important factors affecting gene expression and function, and are closely related to the activation of oncogenes or the inactivation of tumor suppressor genes ( Malhotra et al, 2013 ; Schaefer et al, 2019 ; Visani et al, 2021 ). The results of pan-cancer analysis showed that the USP45 gene had a low frequency of structural variants, mainly present in PRAD and LIHC ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…19 Pancreas cancers are often associated with molecular alterations in the KRAS, TP53, CDKN2A/CDKN2B, BRCA, and SMAD4 genes. 20 Cholangiocarcinoma is an aggressive hepatobiliary neoplasm arising from bile ducts in the liver. There are three main types of cholangiocarcinoma: intrahepatic, perihilar, and extrahepatic.…”
Section: Pathologist Discussionmentioning
confidence: 99%
“…At this time, risk factors associated with the development of PDAC was not clearly established although classical risk factors were suggested as smoking, obesity, age and inflammation ( 81 ). As most cancers, epigenetic and genetic deregulation were observed as Kras mutation observed in >90% for PDAC ( 82 ). PDAC was a very aggressive cancer which rapidly induced metastasis associated to the poor prognosis of this cancer ( 79 ).…”
Section: Anti-tumoral Properties Of Orexins and Receptor Antagonist A...mentioning
confidence: 99%